Toxicity and Hazard of Agrochemicals - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2015)
This edited book, Toxicity and Hazard of Agrochemicals, is intended to provide an overview of toxicology that examines the hazardous effects of common agrochemicals employed every day in our agricultural practices. Furthermore, it is hoped that the information in the present book will be of value to those directly engaged in the handling and use of agrochemicals and that this book will continue to meet the expectations and needs of all interested in the different aspects of human and environmental risk toxicities.